Educational Hall Escape: Increasing Motivation and Raising Emotions in Higher Education Students - Almudena Macías-Guillén; Raquel Montes Díez; Lucía Serrano-Luján; Oriol Borrás-Gené (MDPI AG, 2021)
Educational Escape Room is an innovative method used in classrooms to motivate students. This article describes a version of Educational Escape Room applied to undergraduate students. Specifically, this work presents an adaptation of the method called Educational Hall Escape, characterized by the resolution of challenges in a game-adapted room in which several student groups compete to finish the activity in the least amount of time. To date, the Educational Hall Escape method applied to the field of business economy has not been reported in the literature. The objective of the study is to analyze the influence of the Educational Hall Escape method on the learning processes and emotions of students during the activity and its impact on their motivation and the reinforcement their competences and knowledge. An experiment was designed in which the class was divided into a control group and an experimental group. To measure the impact of the experience in the students, two tools were used: an exam and the Gamefulquest survey. Despite the fact that the results obtained show that the students perceived the experience as a game, it improved their motivation and increased their proclivity to have an emotional bond with the subject, the academic results remained steady.